Furrow Infiltration Methods —A Comparative Study - Tyagi, N.K.; lal, Radhey (Journal of Soil and Water Conservation, 2022)
The present paper makes a comparative study of infiltration by blocking type furrow infiltrometer method and that by volume balance method and presents representative equations for cumulative infiltration depth by both the methods